Validation of the InBody BPBIO250 oscillometric blood pressure monitor for professional office use in general population according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization Universal Standard. Issue 2 (April 2020) - Kollias, Anastasios; Gravvani, Areti; Anagnostopoulos, Ioannis; Kyriakoulis, Konstantinos G.; Bountzona, Ioanna; Menti, Ariadni; Stergiou, George S.
Abstract : Objective: The aim of this study was to evaluate the accuracy of the InBody BPBIO250 oscillometric upper-arm professional office blood pressure (BP) monitor in general population according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Universal Standard (ISO 81060-2:2018). Methods: Subjects were recruited to fulfil the age, gender, BP, and cuff distribution criteria of the AAMI/ESH/ISO Universal Standard in general population using the same arm sequential BP measurement method. Two cuffs of the test device were used for arm circumference 22–32 (medium) and 32–42 cm (large). Results: Ninety-seven subjects were recruited and 88 were analyzed. For validation criterion 1, the mean ± SD of the differences between the test device and reference BP readings was 1.9 ± 5.9/0.9 ± 4.9 mmHg (systolic/diastolic). For criterion 2, the SD of the averaged BP differences between the test device and reference BP per subject was 4.78/4.31 mmHg (systolic/diastolic). Conclusion: The InBody BPBIO250 professional oscillometric device for office BP measurement fulfilled all the requirements of the AAMI/ESH/ISO Universal Standard (ISO 81060-2:2018) in general population and can be recommended for clinical use.